Mexico : Detailed Assessment of Observance of International Association of Insurance Supervisors (IAIS) Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2012)
This paper presents detailed assessment on the observance of Mexico's compliance with the International Association of Insurance Supervisor's Insurance core principles. A new insurance law is expected to be submitted to congress in September 2011, precisely at the time of the mission. The long process in preparing this new insurance law and in gaining consensus of different stakeholders will certainly result in an improvement in compliance with the core principles, and those improvements have been referenced in the assessment.